1995
DOI: 10.1080/00039896.1995.9940887
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Clusters in a Community with Chronic Exposure to Chemicals in Two Superfund Sites

Abstract: Sikes and French, Ltd., two National Priority List sites that are proximal to one another, are located approximately 20 mi (32 km) east of Houston, Texas. Dumping at Sikes occurred during the early 1960s and continued until 1967. Benzene, 1,2-dichloroethane, toluene, 1,1,2-trichloroethane, naphthalene, lead, fluorene, and pyrene are chemicals that pose a particular public health concern. French, Ltd., commenced operations in 1966, and dumping ceased in 1973. Chemicals of potential public health impact at the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Neurological abnormalities were reported in a community exposed to B[a]P, benzofluoranthrene, chrysene, naphthol and pyrene and other PAHs dumped at national priority hazardous waste sites in Texas from the 1960s until the late 1970s 37) . Neurophysiologic and neuropsychological impairments which occurred in residents in Louisiana were related to higher levels of PAHs detected in nearby soils and waters 38) .…”
Section: Discussionmentioning
confidence: 99%
“…Neurological abnormalities were reported in a community exposed to B[a]P, benzofluoranthrene, chrysene, naphthol and pyrene and other PAHs dumped at national priority hazardous waste sites in Texas from the 1960s until the late 1970s 37) . Neurophysiologic and neuropsychological impairments which occurred in residents in Louisiana were related to higher levels of PAHs detected in nearby soils and waters 38) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that As(III) induced HIF-1α through mTOR-dependent pathway in DU145 cells (Skinner et al, 2004). These diverse mechanisms of HIF-1α induction can be operative when several metals were combined, which is a common experience in the real world at superfund sites and in occupational exposure situations (Dayal et al, 1995;Diagomanolin et al, 2004;Roff et al, 2004). As shown in this study, there was synergistic effect on HIF-1α protein level when cells were exposed to the combinations of either [Ni(II) + As(III)] or [Ni(II) + Cr(VI)].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly diverse applications have been seen in studies of water pollution ( e.g., Baker et al, 1978;Lebowitz et al, 1992;Rao et al, 1995 ) and hazardous waste (e.g., Lagakos et al, 1986;Lampi et al, 1992;Gamble and Lewis, 1996;Molholland et al, 1998 ). Exposure indicators using residence location are easy and inexpensive to construct, and increased use is anticipated given advances in geographic information systems (GIS ) and databases that simplify identification of potentially polluted areas (Clark et al, 1982;Budnick et al, 1984;Geschwind et al, 1992;Dayal et al, 1995 ). Some of the exposure indicators require little or even no environmental data, a major contrast to indicators using biological, personal or environmental monitoring.…”
Section: Discussionmentioning
confidence: 99%